Association between functional polymorphisms in IL‐33/ST2 pathway and risk of osteosarcoma. Issue 8 (23rd May 2018) - Wang, Jun‐Li; Liu, Jia; Xie, Ke‐Gong; Lan, Chang‐Gong; Lu, Lu; Tang, Yu‐Jin
Abstract: Interleukin (IL)‐33/ST2 pathway plays crucial roles in tumour growth and metastasis. The aim of this study was to investigate the association of two functional polymorphisms ( IL‐33 rs7025417 and ST2 rs3821204) with osteosarcoma (OS) risk. The rs7025417 and rs3821204 were genotyped by Taqman assay. IL‐33 mRNA and protein levels were measured by real‐time PCR or enzyme‐linked immunosorbent assay. The luciferase activity was measured by a dual luciferase reporter gene assay. The allele‐specific transcription factor binding for rs7025417 was examined by ChIP‐seq. The IL‐33 rs7025417 CC genotype was significantly associated with a decreased risk of OS (CC vs TT: OR = 0.59, 95% CI, 0.41‐0.85; recessive model: OR = 0.68, 95% CI, 0.49‐0.94; C vs T: OR = 0.76, 95% CI, 0.63‐0.91). Combined analysis showed that the IL‐33 rs7025417CT/CC‐ ST2 rs3821204CG/CC and the IL‐33 rs7025417CT/CC‐ ST2 rs3821204GG genotypes also had a decreased risk of OS. IL‐33 mRNA and protein levels in OS patients were significantly higher than controls. Patients with the rs7025417 CC genotype exhibited lower levels of IL‐33 ( P  = .03). The rs7025417 C allele presented a lower transcriptional activity by disrupting the binding site to c‐Myb ( P  <   .01). Moreover, the rs3821204 G/C influences the transcriptional activity and ST2 mRNA expression by altering the binding site of miR‐202‐3p. These findings suggest that the rs7025417 and rs3821204 may have a combined effect to protect against the development of OS by decreasing the expression levels of IL‐33 or ST2 .